Jews against Zionism : the American Council for Judaism, 1942-1948 - Kolsky, Thomas A. (Philadelphia : Temple University Press, 1990)
This is the first full-scale history of the only organized American Jewish opposition to Zionism during the 1940s. Despite extensive literature on the Zionist movement, the Jewish opposition to Zionism has received only marginal and usually negative attention. In this impartial study, Thomas A. Kolsky examines the neglected phenomenon of Jewish anti-Zionism, its roots, and its results. In 1942, a number of dissident Reform rabbis founded the American Council for Judaism, the first and only Jewish organization created to fight against Zionism and the establishment of a Jewish stat.
Preface; Chapter 1: Zionism and Its Reform: Jewish Critichs in America Before World War II; Chapter 2: The Rebellion of the Dissident Reform Rabbis; Chapter 3: The Formation of the American Council for Judaism; Chapter 4: The Council's Wartime Anti-Zionist Campaign; Chapter 5: Between War and Peace; Chapter 6: The Search for Compromise in Palestine; Chapter 7: The Emergence of Israel; Epilogue and Conclusion; Appendix; Notes; Bibliographical Note; Index.
Includes bibliographical references (pages 213-256) and index.
Print version record.
JSTOR
Keywords: American Council for Judaism -- History; American Council for Judaism; American Council for Judaism; Zionism; Jews -- United States -- Politics and government; Zionism and Judaism; Sionisme -- Aspect religieux -- Judaïsme.; POLITICAL SCIENCE -- Political Ideologies -- Nationalism; SOCIAL SCIENCE -- General; Jews -- Politics and government; Zionism; Zionism and Judaism; United States; Antizionismus; USA; Geschichte 1942-1948.; Juden; History